ANALISA KINERJA CNG COOLER PADA SISTEM CNG PLANT - Seno - Darmanto; Muhammad Fahrudin (Gema Teknologi, 2021)
CNG Cooler is a heat exchanger in CNG Plant System which has function to reduce CNG temperature. CNG (Compressed Natural Gas) is natural gas which compressed by gas compressor from normal pressure up to certain high pressure. CNG Plant is gas storage and supply facility for PLTGU when it work at peak load hours. CNG Cooler reduce temperature of CNG which out from gas compressor before saved in storage utility which purpose to avoid over heating in the next process, increase durability of the next process utility, and make gas storage utility design easy.